Sobre Francisco A. Ortega, Rafael E. Acevedo P. y Pablo Casanova Castañeda (eds.), Horizontes de la historia conceptual en Iberoamérica. Trayectorias e incursiones - Echevarría Cázares, Héctor Andrés (Historia Mexicana, 2024)
-